2009
DOI: 10.1016/j.mechmat.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model for drying of a partially saturated porous material

Abstract: a b s t r a c tA new constitutive model for drying of an elastic porous material is presented. The model is derived by decomposing the boundary value problem of drying into parts for which an explicit solution is readily available. The mathematical form differs from models developed using either the concept of equivalent pore pressure or average pore pressure. Instead of pressure averaging, the extent of weakening of the solid due to void inclusions, a material parameter, is found to be critical for the proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 44 publications
1
25
1
Order By: Relevance
“…Several continuum models of deformations induced by RH changes have been proposed [1][2][3]. Typically, these models are based on poromechanics and relate the volumetric strain to the Laplace pressure generated by liquidvapor interfaces in the pore system (also known as capillary stress) [30,52,53].…”
Section: Continuum Modeling Of Reversible Drying Shrinkagementioning
confidence: 99%
See 1 more Smart Citation
“…Several continuum models of deformations induced by RH changes have been proposed [1][2][3]. Typically, these models are based on poromechanics and relate the volumetric strain to the Laplace pressure generated by liquidvapor interfaces in the pore system (also known as capillary stress) [30,52,53].…”
Section: Continuum Modeling Of Reversible Drying Shrinkagementioning
confidence: 99%
“…Evaporable water in cement paste influences important mechanical properties such as drying shrinkage [1][2][3] and creep [4][5][6][7][8][9][10][11]. These influences are due to forces that water and dissolved ions exert from within the complex, multiscale pore system that develops during hydration, i.e., after dry cement powder (mostly calcium silicate minerals) reacts with water.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the solid and of the solid plus pores is explicitly accounted for, and the pressure is reduced by a factor S, which has the effect of averaging the pressure over all of the pores, filled or not. These equations can provide insight and are the subject of continuing research (Vlahinic et al 2008). Understanding porosity is central to understanding volume changes on drying, and if models that predict porosity are developed then properties can be designed from first principles.…”
Section: 3mentioning
confidence: 99%
“…Many researchers have reported that, in this interval, the shrinkage depends on the thickness of the adsorbed water layer on the solid surface (Bentz et al 1998;Feldman and Sereda 1968;Bazant 1988;Vlahinic et al 2009). The shrinkage driving force caused by the increase of surface free energy is dominant while the effect of capillary pressure may be small; the negligible effect of SRA on shrinkage of AAC in this range of RH (Fig.…”
Section: Water Content and Shrinkage Behavior Of Aacsmentioning
confidence: 99%